2019
DOI: 10.1182/bloodadvances.2018028340
|View full text |Cite
|
Sign up to set email alerts
|

Frequent germline mutations of HAVCR2 in sporadic subcutaneous panniculitis-like T-cell lymphoma

Abstract: Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare subtype of peripheral T-cell lymphoma affecting younger patients and associated with hemophagocytic lymphohistiocytosis. To clarify the molecular pathogenesis of SPTCL, we analyzed paired tumor and germline DNAs from 13 patients by whole-exome sequencing. All cases were Asians and were phenotypically sporadic with no family history of SPTCL. Consistent with a recent report, germline mutations in HAVCR2, encoding T-cell immunoglobulin mucin 3 (TIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 27 publications
3
98
0
Order By: Relevance
“…1 Recently, germline mutations causing loss of function of T-cell immunoglobulin mucin 3 (TIM-3) were identified in 60% to 85% of SPTCL patients. 6,7 In these patients, TIM-3 deficiency was shown to promote T-lymphocyte and -macrophage activation and the production of proinflammatory cytokines, challenging the malignant nature of skin T-lymphocyte infiltration. 6 Ruxolitinib is a selective JAK1/JAK2 inhibitor licensed for treatment of myelofibrosis and polycythemia vera in adults.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, germline mutations causing loss of function of T-cell immunoglobulin mucin 3 (TIM-3) were identified in 60% to 85% of SPTCL patients. 6,7 In these patients, TIM-3 deficiency was shown to promote T-lymphocyte and -macrophage activation and the production of proinflammatory cytokines, challenging the malignant nature of skin T-lymphocyte infiltration. 6 Ruxolitinib is a selective JAK1/JAK2 inhibitor licensed for treatment of myelofibrosis and polycythemia vera in adults.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the debate whether TIM3 acts as an inhibitory or a stimulatory molecule, new evidence linking germline HAVCR2 mutations to human disease indicates that TIM3 acts as an inhibitory molecule [144][145][146] . It was shown that mutations in the TIM3 immunoglobulin V domain, c.245A>G (Tyr82Cys) and c.291A>G (Ile97Met), result in misfolding of TIM3 and loss of its expression on the cell surface of both T cells and myeloid cells.…”
Section: Tim3 Germline Mutationsmentioning
confidence: 99%
“…Since the frequency of a homozygous Tyr82Cys mutation in the general population is estimated to be 1 in 35,000, this mutation likely confers high susceptibility to SPTCL 146 . Moreover, one patient with SPTCL carried a heterozygous Tyr82Cys mutation and an additional heterozygous mutation, Thr101Ile.…”
Section: Tim3 Germline Mutationsmentioning
confidence: 99%
“…Sequencing of pre‐hematopoietic stem cell transplantation (pre‐HSCT) PBMC DNA retrospectively established the diagnosis of TIM‐3 deficiency caused by the compound heterozygous mutations p.Ile97Met and p.Thr101Ile in HAVCR2 (Figure S1A). While I97M has been described to abolish protein expression, 4 no expression or functional data have so far been published on the T101I mutation, which has been described in a single patient in association with the Y82C mutation 5 (Figure S1B). Flow cytometry revealed reduced TIM‐3 expression on activated T cells, illustrating that the T101I mutation also leads to reduced protein expression (Figure S1C).…”
Section: Case Descriptionmentioning
confidence: 99%